Analisis Sistem Informasi Penjaminan Mutu Internal pada Universitas Teknologi Digital: Analysis of Internal Quality Assurance Information System at Digitech University - nadia, karina putri; Rudi Hartato, Jarot (Universitas Teknologi Digital, 2025)
The Internal Quality Assurance System (SPMI) is an essential component in higher education management to ensure sustainable educational quality. This research aims to analyze the SPMI information system currently operating at the Digital University, specifically identifying strengths, weaknesses, opportunities, and threats in SPMI management and evaluating the effectiveness of the existing system. The research method used is descriptive qualitative with data collection techniques through observation, structured interviews, and literature study. Data analysis was conducted using SWOT analysis and Flow of Document (FOD) to illustrate the information flow of the running system. The research results show that the SPMI information system at Digital Technology University is still semi-digital in nature, using Microsoft Office and Google Drive for document management. The system's strengths lie in active stakeholder involvement and the implementation team's experience, but it has weaknesses in the form of low efficiency, human error risks, and inadequate documentation. Opportunities for system digitalization and human resource capacity improvement are positive factors, while external policy changes and internal resistance are the main threats. The current system is not yet digitally integrated, causing documentation and reporting processes to be inefficient and prone to errors. This research recommends the development of an integrated web-based SPMI information system and improved human resource training are essential to support the effectiveness of SPMI implementation.